Risk and Islamic banks: a study on Malaysian Islamic banks - Najuna Misman, Faridah; Ahmad, Wahida; Sufiawati Khairani, Noor (International Journal of Engineering and Technology, 2018)
This study examines the major risk faced by Islamic banks specifically in Malaysia. Furthermore, this study also focuses on the risk profile of Islamic banks compared to conventional banks. To achieve the objectives, this study adopts a case study analysis by inverviewing and closely examines the annual reports of four major Islamic banks in Malaysia. The findings reveal that credit risk is the main risk faced by the Islamic banks in Malaysia. Moreover, consistent with the literature, the findings also suggest that specific features of Islamic banks pose an extra and unique risk compared to conventional banks.Â Â